RANCANG BANGUN MESIN ROLLING ADONAN DENGAN PENGGERAK MOTOR LISTRIK DAN TUAS MANUAL - Ichsan Ristiawan; Jasman Jasman; Irmansyah Irmansyah (Dinamika : Jurnal Ilmiah Teknik Mesin, 2019)
East Luwu is a developing district in the economic sector. One of them is a small micro medium business producing bread. Some bakeries still use simple equipment such as manual rollers. The bakery needs a machine that is able to produce flatbread dough with a larger amount, faster time, and the thickness of the bread dough can be adjusted. To support the bakeries, a bread dough peeler is needed to reduce the cost and time. In this study describe the literature study phase and data collection of demands with the parties involved, the design process, manufacturing and testing the machine. The engine drive consists of two modes, the manual crank rotation mode and the 3 phase electric motor mode (380 Volt) with 1390 rpm rotation passed through a two-level pulley-belt transmission system with a ratio of 16, so that it can produce 87 rpm of the roller rotation. Rolling Bread Dough Machine is capable of rolling or flattening bread dough with a thickness of 2 to 15 mm well. thicknesses of 1 to 1.5 mm still need improvement because it produces poorly bread dough and the dough sticks to the machine roller.